2018
DOI: 10.1039/c8cy01484a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ru on the activity of Co3O4 catalysts for chlorinated aromatics oxidation

Abstract: A Ru/Co3O4 catalyst with Ru–O–Co structure presented highly stable activity and selectivity in 1,2-DCB oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 70 publications
1
48
0
Order By: Relevance
“…Co 2p 3/2 and Co 2p 1/2 peaks can be further divided into two sub peaks, which are D 1 (779.7∼780.0 eV), D 2 (781.0∼781.4 eV), D 3 (794.5∼794.6 eV) and D 4 (796.2∼796.4 eV). D 1 and D 3 correspond to octahedral Co 3+ , D 2 and D 4 belong to tetrahedral Co 2+ , which is in accord with the previous report in the literatures [26,50] . The ratios of Co 3+ /Co 2+ were calculated according to the integral area obtained by peak fitting, and the results are recorded in Table 1.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Co 2p 3/2 and Co 2p 1/2 peaks can be further divided into two sub peaks, which are D 1 (779.7∼780.0 eV), D 2 (781.0∼781.4 eV), D 3 (794.5∼794.6 eV) and D 4 (796.2∼796.4 eV). D 1 and D 3 correspond to octahedral Co 3+ , D 2 and D 4 belong to tetrahedral Co 2+ , which is in accord with the previous report in the literatures [26,50] . The ratios of Co 3+ /Co 2+ were calculated according to the integral area obtained by peak fitting, and the results are recorded in Table 1.…”
Section: Resultssupporting
confidence: 86%
“…Co 3 O 4 based catalysts have excellent performances and have been applied in various fields, such as oxidation‐reduction of NO, [17–18] CO oxidation, [19] H 2 production [20] and catalytic oxidation of VOCs [21–23] . Moreover, Co 3 O 4 based catalysts are also widely used in the field of catalytic combustion of CVOCs, e. g., chlorobenzene, [24–26] due to its low O 2 evaporation enthalpy, good bulk oxygen mobility and rich reactive oxygen species [25] . It was reported that the binding bond energy of V−Cl (V=vacancy) is 121 kJ/mol [27] and that of Co−Cl is 117 kJ/mol, [28] which means it only need a little energy to make the catalytic combustion reaction happen spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of o ‐DCB adsorption, a sharp band at 1621 cm −1 is formed, and the intensity increased with time, indicated that the existence of o ‐DCB is the main reason. The wave number of 1461 cm −1 can be attributed to the C=C stretching vibration in the aromatic ring [27] . The weak bands at 1260 and 1125 cm −1 correspond to the plane bending vibration of phenolic compounds, while the adjacent bands which are not obvious at 1032 cm −1 are characterized by C−Cl bond vibration of chlorophenols [28] .…”
Section: Resultsmentioning
confidence: 99%
“…The wave number of 1461 cm À 1 can be attributed to the C=C stretching vibration in the aromatic ring. [27] The weak bands at 1260 and 1125 cm À 1 correspond to the plane bending vibration of phenolic compounds, while the adjacent bands which are not obvious at 1032 cm À 1 are characterized by CÀ Cl bond vibration of chlorophenols. [28] Figure 10b can be more intuitive to see the strip position and change.…”
Section: In-situ Ftir Studies and Reaction Mechanismmentioning
confidence: 99%
“…Considering the high price of precious metals, a certain amount of rare earths has been considered to replace precious metals to prevent reducing the catalytic performance, especially at high space velocities. Due to the larger space velocity under actual working conditions, the experimental space velocity has been increased to 30,000 h −1 [3,28].…”
Section: Introductionmentioning
confidence: 99%